Analysis of genetic parameters on Ethiopian mustard (Brassica carinata A. Braun) genotypes in northwestern Ethiopia - Walle, Tesfaye; Wakjira, Adugna; Mulualem, Tewodros (Plant Breeding and Seed Science, 2014)
This study was carried out with the objective to estimate the genotypic variability and other yield related traits of Ethiopian mustard in North West Ethiopia. A total of 36 genotypes of Ethiopian mustard were considered for this study. Analysis of variance was computed to contrast the variability within the collected genotypes based on yield and other yield related traits. The results revealed highly significant values(p<0.01) for days to maturity, grain filling period, number of pod per plot, secondary branches per plant, harvest index, seed yield per plot, seed yield per hectare and oil content. Significant differences (p<0.05) were noted for days to flowering, plant height, primary branch per plant, biomass per plot, oil yield per plot differences among the genotypes. Genotypic coefficient of variation (GCV %) was lower than phenotypic coefficient of variation (PCV %) for all the traits studied. High genetic advance with heritability was observed in the following characters; plant height, biomass of the plant, number of secondary branch per plant and grain filling period. There are variations in the extent of genetic variability, heritability and genetic advance of traits which can facilitate selection for further improvement of important traits of Ethiopian mustard. Therefore, it can be concluded that the variability within Ethiopian mustard genotypes collected from different areas of northern Ethiopia is high and vital for better crop improvement.